Geographic thought: A Critical introduction - Cresswell, Tim (Hoboken Wiley-Blackwell, 2024)
The fully revised and updated second edition includes A general update bringing the text right up to date with the geographical literature since the first edition was published, including the replacement of examples with interesting up-to-date research from a wider range of geographical contexts A new chapter devoted to physical geography bringing together updated coverage from the first edition with a great deal of new material on this key area for geographic thought Revamped coverage of spatial science and quantitative methods, responding to a range of critiques and bringing quantitative approaches up to date, considering big data and the role of place and specificity in quantitative work Greatly enhanced coverage of GIScience -- which was under-represented in the first edition.